Paternidades e masculinidades: um estudo de representações sociais com homens - Aguilera, Marcello Alves da Silva (2023)
The multiple possibilities of constituting oneself as a man have been increasingly maintained nowadays and, therefore, a dialogue about the role of the exercise of fatherhood in the constitution of masculinities can allow a broader look at this theme. Thus, this study sought to investigate the role of social representations of fatherhood and masculinity in the fatherhood experience of men of fathers, as well as the effects of such an experience in relation to their representations of being a man. The research, with a qualitative approach, counts on the participation of 15 male fathers from different generations of ES. To participate in the study, in addition to being a father and residing in ES, it was necessary to identify with the male gender. In this investigation, parents of generation X (between 46 and 57 years old) and generation Y (between 28 and 45 years old) participated in the study, due to the fact that these two audiences are more accessible through the snowball technique, which is based on indications for the composition of the study sample. Semi-structured interviews guided by a script were carried out with a questions about sociodemographic data and other diverse questions, such as meanings about paternity, masculinity and gender, male participation and division of tasks, care for children and paternal participation, self- perception as a father, among others. For the treatment of data, the phenomenological method for psychological investigation was used, which aims to apprehend the experience in the most genuine way possible, through the reports and experiences of the participants. The results indicated that the path of fatherhood, in the understanding of the participants, both in generation X and in generation Y, impacted the way of behaving as a man, mainly with regard to attributions and responsibilities. However, some understandings regarding “being a father” are still predominant, anchored directly in functions traditionally attributed to men. In any case, new studies that aim to deepen such discussions, especially in psychology, are necessary.